2018
DOI: 10.1038/s41598-018-25560-z
|View full text |Cite
|
Sign up to set email alerts
|

A generalised significance test for individual communities in networks

Abstract: Many empirical networks have community structure, in which nodes are densely interconnected within each community (i.e., a group of nodes) and sparsely across different communities. Like other local and meso-scale structure of networks, communities are generally heterogeneous in various aspects such as the size, density of edges, connectivity to other communities and significance. In the present study, we propose a method to statistically test the significance of individual communities in a given network. Comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 44 publications
0
37
0
Order By: Relevance
“…The package contains an implementation of the MINRES (minimal residual) algorithm 64 , which assigns each node in the perturbome to either the core or the periphery based on a singular value decomposition (SVD) of the adjacency matrix of the network. The statistical significance of the resulting assignment was tested using the ( q , s )-test 65 , which calculates a P value based on a comparison of the core–periphery structure within the perturbome to the core–periphery structure of 1000 randomized networks created using the configuration model.…”
Section: Methodsmentioning
confidence: 99%
“…The package contains an implementation of the MINRES (minimal residual) algorithm 64 , which assigns each node in the perturbome to either the core or the periphery based on a singular value decomposition (SVD) of the adjacency matrix of the network. The statistical significance of the resulting assignment was tested using the ( q , s )-test 65 , which calculates a P value based on a comparison of the core–periphery structure within the perturbome to the core–periphery structure of 1000 randomized networks created using the configuration model.…”
Section: Methodsmentioning
confidence: 99%
“…The modularity maximisation for finding communities in networks also shares this shortcoming 43 . To discuss the CP structure at different resolutions, here we extend the algorithm 6,20 using multiresolution methods 21,22 . In the new algorithm presented in this study, we seek CP pairs by maximisingwhere γ ( γ ≥ 0) is a resolution parameter that controls the effect of the null model term (i.e, ).…”
Section: Methodsmentioning
confidence: 99%
“…We used a label switching heuristic to maximise in our previous algorithms 6,20 . In our preliminary analysis, we found that the label switching heuristic in the present case detected multiple CP pairs in the GLSN for γ = 0, whereas a single CP pair is natural anticipation in this case.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this method leads to a significant reduction of resolution that impairs biological interpretation of the discovered communities [23]. Alternatively, the statistical significance of individual communities can be estimated by comparing them with structures formed in random networks with the same degree characteristics as the original network [13,24,25]. These random networks are typically created using generative models.…”
Section: Introductionmentioning
confidence: 99%